A scoping review of technological interventions to address ethnicity-related peer aggression. (November 2022) - Vandebosch, Heidi; Botezat, Alina; Amodeo, Anna Lisa; Pabian, Sara; Plichta, Piotr; Puharić, Zrinka; Pyżalski, Jacek
Abstract: The past two decades have witnessed an increase in ethnicity-related peer aggression, driven by the intensification of the migration phenomenon and rise of information and communication technologies. The goal of the current study is to extend the scope of previous reviews on peer aggression to examine the emerging evidence on the role of technological tools in the prevention, detection, and handling of ethnicity-related peer aggression among young people. We have identified 14 relevant papers published between 2005 and 2020 that help us answer the following research questions: What forms of aggression among young ethnic minorities do these technological interventions try to address? What types of technological interventions are being used? The results indicate that the technological tools are being used to tackle both intergroup as well as intragroup peer aggression, in which ethnic minorities youth is involved (as a victim, perpetrator or bystander). Most studies have focused on adolescents and young adults in the US or in Europe. The technological tools reported on, include: online games, videos, social media, and chat-based programmes, or machine learning algorithms aimed at tackling online and offline peer aggression. They can be used either as stand - alone tools, or as part of intervention programmes (at the school, family or community level). These findings can be useful to improve and elaborate future digital technologies developed to address ethnicity-related peer aggression. Highlights: The review maps the existing literature on the role of technological tools in tackling ethnicity-related peer aggression. All forms of peer aggression are considered in which ethnic minorities youth was involved. Three groups of technological interventions are identified and categorized into intra- or intergroup ethnicity-related peer aggression. The digital tools presented include: online games, video, social media, chat-based programmes, and machine learning algorithms. Our study reveals some follow-up research questions needed to expand current knowledge on digital technologies.